PENGARUH GAYA KEPEMIMPINAN TERHADAP DISIPLIN SISWA DI SMA ISLAM JAUHARUL FALAH AL-ISLAMY DESA SUNGAI TERAP - Sakinah, Rita; Yudha, Redi Indra (SJEE (Scientific Journals of Economic Education), 2024)
This research aims to determine the influence of the principal's leadership style on the discipline of students at the Islamic SMAjauharul Falah Al-Islamy Sungai Terap Village, Kumpeh Ulu District, Muaro Jambi Regency. The research method used in this research is a quantitative method using simple linear regression analysis techniques. The results of the research show that leadership style has a significant and positive effect on student discipline at the Islamic SMAjauharul Falah Al-Islamy, Sungai Terap Village, Kumpeh Ulu District, Muaro Jambi Regency.